2011
DOI: 10.1093/cvr/cvr018
|View full text |Cite
|
Sign up to set email alerts
|

Placental stem cells pre-treated with a hyaluronan mixed ester of butyric and retinoic acid to cure infarcted pig hearts: a multimodal study

Abstract: Our results support a more pronounced reparative potential of HBR-pre-treated FMhMSCs in a clinically relevant animal model of infarction and highlight the necessity of using combined diagnostic imaging to avoid underestimations of stem cell therapeutic effects in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Recently, it has been indicated that NaBu attenuated gentamicin-induced nephrotoxicity by enhancing renal antioxidant enzyme activity and expression of prohibitin protein (Sun et al, 2013). Moreover, hyaluronan mixed esters of butyric and retinoic acid have also been shown to enhance cardiac repair in infarcted rat and pig hearts (Ventura et al, 2007;Simioniuc et al, 2011). Previously, we have reported that ATRA induces Npr1 gene transcription in cultured mouse mesangial cells (MMCs) in association with E26 transformation-specific 1 (Ets-1), specificity protein 1 (Sp1), and histone acetylation (Kumar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been indicated that NaBu attenuated gentamicin-induced nephrotoxicity by enhancing renal antioxidant enzyme activity and expression of prohibitin protein (Sun et al, 2013). Moreover, hyaluronan mixed esters of butyric and retinoic acid have also been shown to enhance cardiac repair in infarcted rat and pig hearts (Ventura et al, 2007;Simioniuc et al, 2011). Previously, we have reported that ATRA induces Npr1 gene transcription in cultured mouse mesangial cells (MMCs) in association with E26 transformation-specific 1 (Ets-1), specificity protein 1 (Sp1), and histone acetylation (Kumar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of HDACs by RA and SB has also been shown to improve cardiovascular and renal disease conditions (3,5,36). Moreover, mixed esters of butyric acid and retinoic acid hybrid drug (HB) have also been reported to enhance cardiac repair of infarcted hearts in the experimental animals (61,70). In the present study, we examined the effect of RA-, SB-, and HB-mediated effects on the study (30).…”
mentioning
confidence: 96%
“…This finding points at the relevant pleiotropic role of hyaluronic acid (HA) and glycosaminoglycans in the intracrine regulation of cell polarity and at the chance of using physical energies to preserve and direct this fundamental attribute of Life. HA has been used as a component to promote cardiogenesis in mouse embryonic [42] and human adult stem cells of different origin in vitro and in vivo [43][44][45] and to induce cardiac repair in vivo without stem cell transplantation in a rat model of myocardial infarction [46]. Accordingly, HAS2 suppression abolished the capability of human ES cells to differentiate in vitro along the cardiogenic and vasculogenic lineages [47].…”
Section: S4mentioning
confidence: 99%